Therapeutic Effect of Probiotic Dahi on Plasma, Aortic, and Hepatic Lipid Profile of Hypercholesterolemic Rats. (September 2013) - Mohania, Dheeraj; Kansal, Vinod Kumar; Shah, Dilip; Nagpal, Ravinder; Kumar, Manoj; Gautam, Sanjeev Kumar; Singh, Birbal; Behare, Pradip Vishnu
This study examined the effects of probiotic dahi prepared by Lactobacillus plantarum Lp9 and dahi culture in buffalo milk on lowering cholesterol in rats fed a hypercholesterolemic basal diet. Male Wistar rats were divided into 3 groups and fed with probiotic dahi, dahi, or buffalo milk for 120 days. Following the consumption of supplements (probiotic dahi, dahi or buffalo milk), the animals were fed a basal hypercholesterolemic diet. Plasma total cholesterol and triglycerides (TAGs) were decreased by 35% and 72% in rats fed with probiotic dahi group, while cholesterol levels increased by 70% and TAGs increased by 97% in buffalo milk and 59% in dahi fed groups. Supplementation of probiotic dahi further lowered plasma low-density lipoprotein (LDL) + very-low-density lipoprotein (VLDL)- cholesterol by 59%, while it elevated plasma high-density lipoprotein (HDL)-cholesterol by 116%. As a result, atherogenic index, the ratio of HDL to LDL + VLDL was markedly improved. Deposition of cholesterol and TAGs in liver and aorta were significantly reduced in rats fed with probiotic dahi. These observations suggest that probiotic dahi may have therapeutic potential to decrease plasma, hepatic and aortic lipid profile, and attenuate diet-induced hypercholesterolemia.